we can solve this equation by substitution method so

we put y=3x from equation 2 in equation 1

we get

2x-3(3x)=-7

2x-9x=-7

-7x=-7

divide both side by -7 we get

x=1

Now put x=1 in equation 2 , we get

y=3(1)

y=3

so the solution set of these equation is

S.S= {1,3}

I think it is helfull to you If you need more help or you wants to discuss this solution more , so contact me any time , It's pleasure for me to assist you in your problems.

Apr 29th, 2015

Are you studying on the go? Check out our FREE app and post questions on the fly!